DEVELOPMENT OF ENGLISH LANGUAGE LEARNING MODULE FOR THE SIXTH-GRADE ELEMENTARY SCHOOL STUDENTS BASED ON THE MERDEKA CURRICULUM - Marisa Fitri; Iwan Jazadi (GLOBAL: Education Language and Humanity Journal, 2025)
This study aimed to develop an English language learning module for sixth-grade elementary school students based on the Merdeka Curriculum, which emphasizes student-centered, contextual, and differentiated learning. Employing Research and Development (R&D) methodology, the ADDIE model (Analysis, Design, Development, Implementation, Evaluation) was utilized to guide the development process. Data were collected from teacher and student needs analyses, expert validation, and limited trials through interviews, observations, tests, and documentation. The findings revealed that the module development process followed a systematic progression from curriculum alignment and learner analysis to module creation and validation. The resulting module incorporates thematic and contextual content, project-based tasks, visual and linguistic scaffolding, and reflective activities to support various student learning styles. Expert validation and field testing confirmed the module’s feasibility and effectiveness in enhancing students’ English learning outcomes, particularly in vocabulary acquisition, speaking confidence, and integrated skill practices. This study suggests that a well-designed and validated module aligned with the Merdeka Curriculum can serve as an effective teaching and learning tool to support English instruction in elementary education